2016
DOI: 10.1080/15476286.2016.1227905
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs: Unexpected outputs of many protein-coding genes

Abstract: Pre-mRNAs from thousands of eukaryotic genes can be non-canonically spliced to generate circular RNAs, some of which accumulate to higher levels than their associated linear mRNA. Recent work has revealed widespread mechanisms that dictate whether the spliceosome generates a linear or circular RNA. For most genes, circular RNA biogenesis via backsplicing is far less efficient than canonical splicing, but circular RNAs can accumulate due to their long half-lives. Backsplicing is often initiated when complementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
86
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 105 publications
(241 reference statements)
0
86
0
Order By: Relevance
“…CircRNAs result from back‐splicing events from protein‐coding genes and can accumulate to much higher levels than their associated linear transcript (Wilusz, 2017). Recent studies have shown that depletion of spliceosomal components in Drosophila cells increases levels of circRNAs, while reducing levels of their associated linear mRNA (Liang et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…CircRNAs result from back‐splicing events from protein‐coding genes and can accumulate to much higher levels than their associated linear transcript (Wilusz, 2017). Recent studies have shown that depletion of spliceosomal components in Drosophila cells increases levels of circRNAs, while reducing levels of their associated linear mRNA (Liang et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Circular RNAs are a recently described class of stable RNAs that are naturally resistant to degradation by exonucleases and are generated from thousands of protein-coding genes (reviewed in Chen, 2016; Ebbesen et al, 2016; Wilusz, 2016). The mature transcripts contain almost exclusively exonic sequences, have covalently linked ends, and are generated when the pre-mRNA splicing machinery “backsplices” to join a downstream splice donor to an upstream splice acceptor (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These studies identified hundreds of previously unknown RBPs bound to mRNAs in human cell lines (Baltz et al, 2012; Beckmann et al, 2015; Castello et al, 2012; Conrad et al, 2016) and mouse embryonic stem cells (ESCs) (Kwon et al, 2013). However, most small RNAs and many lncRNAs are not polyadenylated, including abundant nuclear RNAs like MALAT1 (Brown et al, 2012; Wilusz et al, 2012), enhancer-derived RNAs (eRNAs) (Lam et al, 2014), and circular RNAs (Wilusz, 2016). Proteins interacting with these and other polyA − ncRNAs have thus been missed by existing approaches.…”
Section: Introductionmentioning
confidence: 99%